Simplify ln(e^2) - 4ln(1/e)

Using log rules, we can simplify the equation as follows: Firstly log(xa) = alog(x) implies that ln(e2) = 2ln(e). Next loga(a) = 1 implies 2ln(e) = 21 = 2 [Since the natural logarithm ln is equivalent to loge]. So ln(e2) = 2. Following this ln(1/e) = ln(e-1), which from the previous rule we can see ln(e-1) = -ln(e). Lastly we know ln(e) = 1, so -4*-ln(e) = -4*-1 = 4. So -4ln(1/e) = 4. Therefore ln(e2) - 4ln(1/e) = 2 + 4 = 6

Answered by Mark J. Maths tutor

4385 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Solve the inequality x^2 - 9 > 0


Why is the derivative of ln(x) equal to 1/x.


How do I know which is the null hypothesis, and which is the alternative hypothesis?


How do you integrate the natural logarithm ln(x)?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences